Expression of Myostatin Gene in Belgian Blue and Ongole Grade Crossbred Cattle - Winni Liani Daulay; Putri Indah Ningtias; Cece Sumantri; Jakaria Jakaria (Buletin Peternakan, 2022)
Investigating Myostatin (MSTN) as a potent inhibitor of skeletal muscle growth and development to produce excessive muscles is extremely essential for livestock breeding. This study aimed to analyze the expression of the MSTN gene and its relationships with genotype and phenotype (normal-muscled vs double-muscled) of Belgian Blue (BB) x Ongole Grade (PO) crossbred cattle. For that purpose, 12 animals from BB, PO, BB x PO F1, and BB x PO F2 cattle (3 animals each) raised at Balai Embrio Ternak (BET) Cipelang Bogor, West Java were used for blood sample collection. Genotyping analysis was performed using the PCR-RFLP method withprimer F: 5’-CTC TTC TTT CCT TTC CAT ACA GAC-3’ and R: 5’-AGG GGA AGA CCT TCC ATG TT-3’, while the MSTN gene expression was analyzed using the qPCR technique. As results, three genotypes: del.11/del.11, +/del.11, and +/+ were detected. The del.11/del.11 genotype, which showed a double-muscled phenotype was found in BB cattle and BB x PO F2 cattle. The +/del.11 genotype was found in BB x PO F1 cattle and BB x PO F2 cattle. The +/+ genotype, which showed a normal phenotype was only detected in PO cattle. There was a significant difference of the MSTN gene expression in the sampled animals among genotypes and between phenotypes (normal-muscled vs double muscled). The MSTN expression in animals with del.11/del.11 genotype was higher than that in animals with +/del11 and +/+ genotypes (P<0.05). Animals with +/+ genotype showed the lowest MSTN expression. It was concluded that double-muscled animals showed higher MSTN expression than normal-muscled animals.